Characterization of four red hybrids tilapia (Oreochromis sp.) through morphometric characteristics. - Zharif Ramli; Wan Zahari M.; Lee S.W.; Ibrahim C.O. (Academia Publishing, 2016)
This study was performed to characterize and evaluate four red hybrids of tilapia aimed to produce table fish with economic traits. Four hybrids were produced namely: ON, OM, MN and NM. Twenty-three (23) morphometric landmarks were evaluated and results showed nine characteristics such as Body width (Bw1), Distance from end of dorsal ray to 1st anal fin (D1da), Distance from caudal to anal fin (DcaL), Body height (BH), Pre-pectoral length (PCL), Pre-pelvic length (PPL), pre-anal length (PAL), Pre-orbital length (POL) and Pelvic fin length (PlvL) were observed to be significantly different (p<0.05) between hybrids. Hybrid ON had greater morphological ratio in leven (11) characteristics followed by hybrid MN, OM and NM. Hierarchical cluster analysis characterized the similar morphological characteristics shown in the dendogram which illustrated two distinct groups consisting of two strains; Group 1: OM and Group 2: ON. In addition, group 2 formed monophyletic groups which included hybrids NM and MN. Biometric analysis exhibited the morphological conformation and variation between hybrids which can be subjected to further improvement.